Pembelajaran dan Pengajaran Tata Bahasa Berdasarkan Korpus - Herpindo Herpindo; Astuty Astuty; Mursia Ekawati; Gilang Fadhilia Arvianti; Miftahula Rizqin Nikmatullah; Muhammad Nur Afiq (Risenologi, 2023)
This study is prompted by the advancement of corpus-based methods in the realm of grammar education. The primary objective of this research is to assess the requirements and the perceived significance of integrating corpus linguistics into the methodologies of grammar instruction. Employing an experimental research approach, the study involves participants who are undergraduate students majoring in Indonesian Language and Literature Education as well as English Language Education. The research utilizes the Leipzig Indonesian Mix_2013 and English-corpus.org corpora. The outcomes of this investigation offer an insight into the teaching of grammar through the incorporation of corpora, drawing comparisons based on the outcomes prior to the experimental sessions. The findings from this study highlight that the implementation of corpus linguistics within grammar learning and teaching methodologies yields a favorable impact on students' comprehension of grammar rules. The analysis of needs underscores students' recognition of the importance of integrating corpus elements into grammar education, particularly given the diverse and evolving language contexts prevalent in daily life. This perception is further reinforced by the results of the experimental phase, which demonstrate a substantial enhancement in grammar comprehension within the group exposed to corpus-based instruction. The deeper understanding gained regarding the real-world application of grammar in communicative scenarios equips students with enhanced readiness to apply grammatical concepts effectively in practical contexts. In conclusion, this research underscores the pivotal role of corpus linguistics in augmenting the efficacy of grammar education. The study provides valuable insights into the potential advantages associated with the integration of corpus-driven methodologies into language instruction, considering the dynamic nature of language usage in contemporary society. Furthermore, the outcomes emphasize the significance of aligning teaching practices with the evolving landscape of language usage.